Nodule carbohydrate catabolism is enhanced in the Medicago truncatula A17-Sinorhizobium medicae WSM419 symbiosis - Larrainzar, Estíbaliz (Frontiers Media S.A., 2014)
The symbiotic association between Medicago truncatula and Sinorhizobium meliloti is a well-established model system in the legume–Rhizobium community. Despite its wide use, the symbiotic efficiency of this model has been recently questioned and an alternative microsymbiont, S. medicae, has been proposed. However, little is known about the physiological mechanisms behind the higher symbiotic efficiency of S. medicae WSM419. In the present study, we inoculated M. truncatula Jemalong A17 with either S. medicae WSM419 or S. meliloti 2011 and compared plant growth, photosynthesis, N(2)-fixation rates, and plant nodule carbon and nitrogen metabolic activities in the two systems. M. truncatula plants in symbiosis with S. medicae showed increased biomass and photosynthesis rates per plant. Plants grown in symbiosis with S. medicae WSM419 also showed higher N(2)-fixation rates, which were correlated with a larger nodule biomass, while nodule number was similar in both systems. In terms of plant nodule metabolism, M. truncatula–S. medicae WSM419 nodules showed increased sucrose-catabolic activity, mostly associated with sucrose synthase, accompanied by a reduced starch content, whereas nitrogen-assimilation activities were comparable to those measured in nodules infected with S. meliloti 2011. Taken together, these results suggest that S. medicae WSM419 is able to enhance plant carbon catabolism in M. truncatula nodules, which allows for the maintaining of high symbiotic N(2)-fixation rates, better growth and improved general plant performance.